PENGARUH STRATEGI DIFERENSIASI TERHADAP LOYALITAS PELANGGAN (STUDI KASUS TOKO BUKU ZANAFA) METROPOLITAN CITY PEKANBARU - Defi Mariyana; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research was conducted at Zanafa Bookstore located on Jl HR. Subrantas Metropolitan City Complex (MTC) / GIANT. The purpose of this study was conducted to determine the effect of Differentiation Strategies on Customer Loyalty in Zanafa Bookstore.In this research the methodology used is descriptive and quantitative with SPSS program, where the population in this research is the customer in Zanafa Bookstore. For sampling using slovin formula, the sampling method with accidental sampling is as many as 100 people. The research data are primary data and secondary data, with questionnaire as research instrument.From the results of data analysis that includes test validity, reliability, simple linear regression, test determination (R2) and t-test. The results showed that differentiation strategy significantly influence customer loyalty. This can be seen from the value of tcount (4.201)> ttabel (1,984). So that the number obtained R. Square (R2) of 0.153. This shows that the percentage of contribution of independent variable (Differentiation Strategy) to the bonded variable (Customer Loyalty) is 15.3% and the relationship given is weak by 0.15. While the remaining percentage of 84.7% (100% - 15.3%) is influenced by other variables that are not included or not observed in this research.Keywords: Differentiation Strategy, Customer Loyalty